Simulation study on the electric field characteristics of ice-covered insulator for catenary positive feeder - Yuantao Liu; Shanpeng Zhao; Yanzhe Li; Youpeng Zhang; Sihua Wang (Energy Reports, 2023)
To study the electrical characteristics of ice-covered insulators, this paper uses the finite element method to simulate the BXN-25 type insulator of the positive feeder of the catenary under three icing conditions of different icing thickness, icicle length, air gap position, and compares it with the clean insulator. The research shows that icing on the surface of the insulator shed will reduce the insulation distance, thus affecting the insulation performance of the insulator. The electric field distributions are also different with the different number of icicle bridge insulator sheds. When the icicle bridge is connected to different positions of the insulator shed, the air gaps at different positions will be generated. The amplitude of the air gap will increase sharply when it is located at the low-voltage end, making the insulator more prone to flashover.